2018
DOI: 10.1177/0885066618768749
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Continuous Infusion Vancomycin Administration in a Critically Ill Trauma Population

Abstract: Vancomycin is a first-line antibiotic for empiric treatment of gram-positive infections in the trauma intensive care unit. When dosed intermittently, difficulties arise from trough collection and drug monitoring. The objective of this study was to evaluate time to goal vancomycin levels comparing a continuous infusion protocol when compared to standard intermittent infusion dosing. This was a retrospective cohort of patients admitted to the trauma intensive care unit between July 2011 and July 2015 receiving v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Because no comparative study on efficacy and safety between continuous and intermittent infusion therapy based on AUC-guided dosing is available, vancomycin continuous infusion is not currently recommended [ 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 ] (III-B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because no comparative study on efficacy and safety between continuous and intermittent infusion therapy based on AUC-guided dosing is available, vancomycin continuous infusion is not currently recommended [ 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 ] (III-B).…”
Section: Resultsmentioning
confidence: 99%
“…Bissell et al reported that the continuously infused vancomycin had a shorter time to target achievement with a higher incidence of target attainment than intermittently infused vancomycin in critically ill patients, which resulted in a lower average number of blood samples per patient and shorter duration of therapy [ 181 ]. A recent meta-analysis of RCTs and observational studies for critically ill adult patients reported by Flannery et al demonstrated that continuous infusion was associated with a lower AKI risk (OR = 0.47, 95% CI = 0.34–0.65) and a higher PK target attainment rate (OR = 2.63, 95% CI = 1.52–4.57) than intermittent infusion [ 176 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients' clinical parameters were extracted mainly based on previous studies. 3,6,7,9,[12][13][14][15][16][17][18][19][20][21][22][23]26,27…”
Section: Data Extractionmentioning
confidence: 99%
“…6,12 With the aging of our society, VANT in elderly patients is worthy of more attention. 12 Previous studies indicate that age, 7 mechanical ventilation, 12 intensive care unit (ICU) admittance, 13 vancomycin trough concentration, 9,14-17 dose, 15 length of therapy, 9,17 infusion method (continuous or intermittent infusions), 18,19 cirrhosis, 14 hypertension, 20 hyperuricemia, 12 shock, 6 heart failure, 6 concomitant medications, vasopressor drugs, 16,17 aminoglycosides, 9,21 contrast agents, 22,23 piperacillin/tazobactam (PTZ), 24,25 furosemide, 3,11 amphotericin B, 26 and the Acute Physiology and Chronic Health Evaluation II (APACHE-II) 21,27 are risk factors associated with VANT. However, only two studies reported VANT risk factors in elderly patients.…”
mentioning
confidence: 99%
“…In critically ill patients, more current studies on vancomycin II vs. CI have focused mainly on the comparison in terms of the efficacy and safety of vancomycin ( Vuagnat et al., 2004 ; Hutschala et al., 2009 ; Akers et al., 2012 ; Saugel et al., 2013 ; Schmelzer et al., 2013 ; Hanrahan et al., 2014 ; Tafelski et al., 2015 ; Bissell et al., 2020 ). However, comparative studies on the outcomes of vancomycin II vs. CI against MRSA isolates with a specific MIC are still scarce.…”
Section: Discussionmentioning
confidence: 99%